2019
DOI: 10.20524/aog.2019.0418
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of acute esophageal necrosis

Abstract: Acute esophageal necrosis is a rare syndrome classically characterized by a striking endoscopic image of diffuse and circumferential black mucosal discoloration of distal esophagus, with an abrupt transition at the gastroesophageal junction and variable proximal extension. The typical patient is an older male with general debilitation and multiple comorbidities presenting with hematemesis or melena. The pathophysiology usually involves a combination of esophageal ischemia, backflow injury from gastric chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
123
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(139 citation statements)
references
References 108 publications
(220 reference statements)
4
123
1
11
Order By: Relevance
“…Several drugs have been involved in this pathophysiology of AEN, including non-steroidal anti-inflammatory drugs (NSAID), antihypertensive agents, terlipressin, clozapine, olanzapine, cocaine, and Immunosuppressant agent. [ 1 , 12 ] Esophageal ischemia may be induced by vasoconstrictive agents such as terlipressin, and antihypertensive agents which induce transient low circulatory flow. Immunosuppressant agents like Tacrolimus and MMF compromise gastrointestinal mucosa ability to local defense barrier function and increase the risk of opportunistic infection such as CMV esophagitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several drugs have been involved in this pathophysiology of AEN, including non-steroidal anti-inflammatory drugs (NSAID), antihypertensive agents, terlipressin, clozapine, olanzapine, cocaine, and Immunosuppressant agent. [ 1 , 12 ] Esophageal ischemia may be induced by vasoconstrictive agents such as terlipressin, and antihypertensive agents which induce transient low circulatory flow. Immunosuppressant agents like Tacrolimus and MMF compromise gastrointestinal mucosa ability to local defense barrier function and increase the risk of opportunistic infection such as CMV esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressant agents like Tacrolimus and MMF compromise gastrointestinal mucosa ability to local defense barrier function and increase the risk of opportunistic infection such as CMV esophagitis. [ 12 , 13 , 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal injury in AEN results predominantly from a combination of ischemic injury and gastroesophageal acid reflux‐mediated mucosal damage. Most cases occur in patients with underlying cardiovascular comorbidities and alcohol use and are typically associated with cases of severe hemodynamic instability and low‐flow states 3 . Presenting symptoms can include hematemesis, melena, nausea, vomiting, abdominal pain, dysphagia, or odynophagia 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It was first described in the medical literature in 1990 by Goldenberg et al, and was brought into the spotlight in 2007 by Gurvits et al (1,2). In endoscopic examinations, the prevalence of AEN is rare and reported to be up to 0.28% (3,4). The precise etiology of the disease remains unknown, but is presumed to be multifactorial with mucosal ischemia, injury by the reflux of gastric chemical contents, and an impaired mucosal barrier associated with debilitated physical states (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In endoscopic examinations, the prevalence of AEN is rare and reported to be up to 0.28% (3,4). The precise etiology of the disease remains unknown, but is presumed to be multifactorial with mucosal ischemia, injury by the reflux of gastric chemical contents, and an impaired mucosal barrier associated with debilitated physical states (3,4). It has been reported that patients usually present multiple comorbidities, the most common being diabetes mellitus, followed by hypertension, alcohol abuse, chronic kidney disease, coronary heart disease, dyslipidemia, peripheral artery disease, malignancy, liver cirrhosis, gastroesophageal reflux disease, congestive heart failure, and chronic obstructive pulmonary disease (5).…”
Section: Introductionmentioning
confidence: 99%